2005
DOI: 10.5713/ajas.2005.502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Level of Crude Protein and Use of Cottonseed Meal in Diets Containing Cassava Chips and Rice Straw for Lactating Dairy Cows

Abstract: The effects of different levels of crude protein (CP) and cottonseed meal replacing for soybean meal in cassava chips and rice straw-based diets for mid-lactating cows (100-150 day in milk [DIM]), were studied using 32 multiparous Holstein Fresian crossbred dairy cows. Diets containing 10.5, 12.5, 13.7, 14.4% CP of the rations and 0, 12.1, 14.9, 17.8% cottonseed meal were fed to cows for 60 days. Thirty two cows were randomly divided into four dietary treatments using a Randomized complete block design. Four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
5
24
0
Order By: Relevance
“…The MUN values were significantly affected by dietary treatments (P < 0.01), with the lowest values in cows fed diet A, followed by diets B and C, and the highest in cows fed diet D. The MUN values increased with CP levels. The observation was consistent with some studies (Davidson et al, 2003;Groff and Wu, 2005;Promkot and Wanapat, 2005), while Flis and Wattiaux (2005) found that a 1% change in the dietary protein level did not cause a significant change in the MUN content.…”
Section: Resultssupporting
confidence: 81%
“…The MUN values were significantly affected by dietary treatments (P < 0.01), with the lowest values in cows fed diet A, followed by diets B and C, and the highest in cows fed diet D. The MUN values increased with CP levels. The observation was consistent with some studies (Davidson et al, 2003;Groff and Wu, 2005;Promkot and Wanapat, 2005), while Flis and Wattiaux (2005) found that a 1% change in the dietary protein level did not cause a significant change in the MUN content.…”
Section: Resultssupporting
confidence: 81%
“…The increased blood urea‐N concentration in the lambs fed CSL was in association with the higher ruminal ammonia‐N in them (Table ). Findings of Promkot and Wanapat () and Azizi‐Shotorkhoft et al. () have also shown a positive correlation between blood urea‐N and ruminal ammonia‐N concentrations.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, cottonseed meal, an important rumen undegradable protein source (49 g/kg DM; Shibanda et al 1992), could be beneficial for improvement of animal performance. Promkot and Wanapat (2005) concluded that using cottonseed meal as the main source to completely replace soybean meal was beneficial to cows consuming rice straw and cassava chips-based diets. This agreed with Wanapat et al (1996) who found that cottonseed meal supplementation significantly increased milk yield of dairy cattle fed rice straw.…”
Section: Introductionmentioning
confidence: 98%